Explaining the Link Between Personality and Relationship Satisfaction: Emotion Regulation and Interpersonal Behaviour in Conflict Discussions. Issue 2 (March 2015) - Vater, Aline; Schröder‐Abé, Michela
Abstract: Past research has shown that personality traits predict relationship quality in romantic couples. However, very little research has investigated psychological processes that underlie the link between personality and relationship satisfaction. The present study focused on the mediating role of spontaneous emotion regulation and positive interpersonal behaviour. This study applied a dyadic design with 137 couples who completed self‐report questionnaires assessing Big Five personality traits at baseline. Subsequently, couples were asked to discuss a current relationship conflict during a laboratory session. Emotion regulation and relationship satisfaction were assessed via self‐report directly after the discussion. Relationship satisfaction was additionally assessed at 6‐month follow‐up. Interpersonal behaviour during the conflict discussion was videotaped and coded by independent raters. As expected, emotion regulation (expressive suppression, perspective taking and aggressive externalisation), positive interpersonal behaviour and state relationship satisfaction during the conflict discussion mediated the relation between personality and long‐term relationship satisfaction. In sum, this study provides evidence that personality is linked to relationship satisfaction through intrapersonal and interpersonal processes during social interactions. Copyright © 2015 European Association of Personality Psychology